Model Analysis and Laboratory Experiments of Strengthening Diagonal Wall Panels in Concrete Structures - Nurchasanah, Yenny; Ujianto, Muhammad (Universitas Muhammadiyah Surakarta, 2015)
Walls, even though being included in non-engineering building element, actually have the strength and stiffness. In this study, the wall elements will be analyzed regarding the influence in a system of reinforced concrete frame. The other side of this research is the adoption of high-rising building technology in the use of shear wall elements into earthquake-safe homes.This technology is to prevent the wall from quick collapse when exposed to seismic forces are by strengthening the areas diagonally. Diagonal area is an area where there will be the greatest shear force effects, and it is characterized by the appearance of cracks or even splitting on the diagonal area. The modeling of reinforced concrete structures is applied to SAP2000 to open frame and frame with concrete panels as filler. This is modeled as bracing representing an area of wall. There are 37 test objects of open frame and frame with wall concrete panels as filler (100x50x7), with diagonal reinforcement/bracing of the group of steel reinforcing. SAP2000 analysis results indicate that the structure with wall panels have a higher value than the capacity of open frame structure. Laboratory experimental data with compression test showed increased values up to 215.36% on the frame with wall panel, an increase of 271.99% on the frame wall panels with diagonal steel reinforcement. Flexural test showed increased values up to 37.73% on the frame with wall panel and an increase of 260.76% on the frame wall panels with diagonal steel reinforcement. The addition of diagonal reinforcement elements is conducted to divide the force received by the wall and to increase the strength of the wall and the stiffness of the structural system.